The Effect of Supply Chain Integration, Management Commitment, and Sustainable Supply Chain Practices on the Performance of Craft MSMEs in Bantul Regency - Luki Antoro; Titik Kusmantini; Nilmawati Nilmawati (AIBPM Publisher, 2025)
This study examines the effects of Supply Chain Integration (SCI) and Management Commitment (MC) on the performance of handicraft MSMEs in Bantul Regency. Drawing on the Natural Resource-Based View and Dynamic Capabilities Theory, the study investigates the role of Sustainable Supply Chain Practices (SSCP) as a mediating variable and Supply Chain Challenges (SCC) as a moderating variable. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) based on survey data collected from 100 owners and managers of verified handicraft MSMEs in Bantul Regency, Indonesia. The results indicate that Supply Chain Integration and Management Commitment have significant positive effects on both Sustainable Supply Chain Practices and MSME performance. Sustainable Supply Chain Practices also have a significant positive effect on MSME performance. However, SSCP does not significantly mediate the relationships between SCI, MC, and MSME performance. Furthermore, Supply Chain Challenges significantly moderate the relationship between SSCP and MSME performance